Kekuatan Alat Bukti Petunjuk Dalam Perkara Tindak Pidana Korupsi - Ony Rosifany (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2016)
The attitude of the judge in determining the evidence leads, which are listed in Article 188 paragraph (3) Criminal Procedure Code (KUHAP) requires the judge to do so wisely longer wise, because the these instructions evidence fully addressed the judge hence the assessment of the strength of proof should be done by the judge wisely, thoughtful and objective.            Combating corruption can not be done only by the Commission and law enfor, but also requires a synergy and a common perception of all components of the nation. Community participation is needed and has significance in corruption eradication strategy. In activities that are repressive, the public could be the pioneer of allegations of corruption, especially in the bureaucracy and public services, while on the preventive side, the main measures to eradicate corruption can be started from the consciousness of an individual to obey the law and avoid corruptive behavior.            Strength of evidence hint of valid evidence in a corruption case and the use of evidence in the instructions as a basis the judgment.